2016
DOI: 10.5897/jphe2015.0781
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer knowledge and screening practices among female secondary schools teachers in an urban local government area, Ibadan, Nigeria

Abstract: Breast cancer a major public health challenge is often associated with high morbidity which often times is not unconnected with poor knowledge and screening practices. Teachers who are seen as role model are the key stakeholders in prevention of breast cancer (BC). However their knowledge and screening practices have not been fully explored. Therefore this study was designed to investigate knowledge of breast cancer and screening practices of female Senior Secondary (SS) school teachers in an urban local gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
(24 reference statements)
5
13
5
Order By: Relevance
“…In this study, 86% of participants were aware that mammogram was recommended above 40 years and this result was found in a group of women with good knowledge about healthy lifestyle and healthy practices including spacing between births and family planning [20]. This result disagrees with Ojewusi and Arulogun's study [4] in which only 3.3% identified the age of 40 as a recommended age for mammogram screening. According to Milicent et al [20], women who were most likely to benefit from mammography aged 50 to 69 years, as this age had high prevalence of low breast density.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…In this study, 86% of participants were aware that mammogram was recommended above 40 years and this result was found in a group of women with good knowledge about healthy lifestyle and healthy practices including spacing between births and family planning [20]. This result disagrees with Ojewusi and Arulogun's study [4] in which only 3.3% identified the age of 40 as a recommended age for mammogram screening. According to Milicent et al [20], women who were most likely to benefit from mammography aged 50 to 69 years, as this age had high prevalence of low breast density.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding agreed with Boulos and Ghali [16] study among Ain Shams University female students aged from 17 to 23 years, who showed that most study participants had low level of knowledge about breast cancer risk factors. More than 85% of study participants knew that mammogram was recommended above the age of 40 which disagrees with Ojewusi and Arulogun's study, 2016, in their Nigerian study [4]. They found that 1.6% only of their participants knew that 40 years is the recommended age for mammogram.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations